Zinc has a role in pathogenesis of pityriasis alba - Fatma M Elesawy; Essam M Akl; Walid A Abdel Halim (Indian Journal of Paediatric Dermatology, 2020)
Background: Pityriasis alba (PA) is a common disease of children and seen in most of the developing countries. The exact pathogenesis of PA is still not well established. Some cases of PA have been associated with atopic dermatitis, while most cases have no association with it. Objectives: The objective was to evaluate the role played by zinc (Zn) in the pathogenesis of PA. Patients and Methods: Sixty patients suffering from PA were included in the study, and 30 apparently healthy individuals of matching age and sex were recruited as a control group. Serum Zn, hemoglobin, and albumin were measured in both groups. In addition, skin phototype and body mass index were recorded. The American Academy Criteria of atopic dermatitis diagnosis were applied to the participants in this study. PA patients were examined dermatologically with a recording of the site, size, and number of lesions. Results: There was no difference in the presence of atopic dermatitis between the patient and control groups (P = 0.672). PA lesions were detected in the faces of all patients. There were no statistically significant differences between patients and controls regarding serum hemoglobin concentration (P = 0.763) or serum albumin (P = 0.487). The serum level of Zn was lower in patients with PA than controls (P < 0.001) with statistically significant positive correlations with both numbers and size of PA lesions (P < 0.001 and P = 0.011, respectively). Conclusions: The present study showed that Zn may have a role in PA, and oral supplementation with Zn may be considered as a therapeutic approach in this disease.